REASONS FOR LATE PRESENTATION OF CLEFT DEFORMITY IN NORTHEASTERN NIGERIA - O.A ADESINA; H.O OLASOJI; V I UGBOKO (Ntec Specialist, 2010)
Background: Cleft lip and palate is the commonest congenital deformity of the orofacial region. It is generally accepted that the surgical operations of cleft lip and palate should be done early in life. In developing countries, a significant number of these patients present for treatment in late childhood and in some instances as adults. The precise reasons for this will most certainly vary from culture to culture, but the common reasons may be quite similar in many countries. Method: Fifty-two patients with facial clefts who presented late at the University of Maiduguri Teaching Hospital within a 2-year period were assessed by interviewing either the parents, relations or even the patients themselves. Result: The reasons for late presentation were financial constraint (46%), lack of knowledge of availability of cleft services (40%), far distance from cleft centre (8%), cultural beliefs (4%) and fear of surgery (2%). Conclusion: The result of this study revealed financial constraint and lack of knowledge of availability of cleft services as prominent reasons why majority of patients with cleft deformity presents late. Adequate funding of cleft care from both government and non-governmental organisations, providing primary health care workers with information regarding the availability of cleft services and improved public enlightenment programme would reduce the rate of late presentation in Nigeria and other developing countries